1977
DOI: 10.1159/000114829
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Efficacy of Waking and Sleep Recordings following Sleep Deprivation as an Activation Method in the Diagnosis of Epilepsy

Abstract: In the present work, on the basis of an unselected collection of patients suspected of epilepsy, the diagnostic value of waking and sleep recordings each after 24 h sleep deprivation are compared with one another. Indicative findings of epilepsy were found in 16.7 % of the cases in the waking EEG after sleep deprivation. In the sleep EEG after sleep deprivation this amounted to 57.1 %. These figures speak for the advantage of the second method. The result is highly significant with a x2 value of 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Some authors (Scollo-Lavizzari et al, 1977;Ritter et a l, 1977;Schwarz and Zangemeister, 1978) pointed out the greater efficacy of sleep records after sleep deprivation. Such rigid dis tinction was impossible in our cases; in fact we recorded dozing or sleep in the first period or, on the contrary, we could not record sleep in the second period.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (Scollo-Lavizzari et al, 1977;Ritter et a l, 1977;Schwarz and Zangemeister, 1978) pointed out the greater efficacy of sleep records after sleep deprivation. Such rigid dis tinction was impossible in our cases; in fact we recorded dozing or sleep in the first period or, on the contrary, we could not record sleep in the second period.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with epilepsy and a normal or inconclusive routine EEG, sensitivity values ranged from 20% (So et al, 1994) to 57% (Scollo-Lavizzari et al, 1977). In a well-characterized population of epileptic adults with a normal first EEG, we have recently shown an overall IED incidence of 42.1% after SD: 39.6% in focal symptomatic epilepsies; 37.5% in probably symptomatic epilepsies; and 57.2% in generalized epilepsy patients.…”
Section: Sensitivity and Specificity Of Sd Eegmentioning
confidence: 95%
“…Fountain et al (1998) specifically addressed this aspect and showed significant IED incidence both during wakefulness and sleep SD EEG epochs, inferring that the EEG activation was exclusively due to SD, rather than to the occurrence of sleep. Conversely, other authors suggested that EEG activation after SD might be related to the time spent in sleep or in drowsiness (PeraitaAdrados et al, 2001;Veldhuizen et al, 1983), or to a combination of the provocative effects of both SD and sleep/drowsiness (Geller et al, 1969;Scollo-Lavizzari et al, 1977). Roupakiotis et al (2000) reported that no specific conclusions about the contribution of sleep to the efficacy of SD could be drawn, after finding a similar activation rate in SD EEGs with and without sleep epochs.…”
Section: Specific Effect Of Sd or Simple Effect Of Drowsiness/sleep?mentioning
confidence: 97%
“…Several studies have shown that TSD is equally if not more effective in children with epilepsy (Bechinger et al, 1976;Degen et al, 1980;Degen et al, 1981;Geller et al, 1969;Roth et al, 1986;Tartura et al, 1980). Table 2 summarizes findings of comparative studies that largely confirm that TSD activates IEDs in 23% to 93% of patients with definite or suspected seizures (Aguglia et al, 1994;Bechinger et al, 1973;Degen et al, 1987;Donzal et al, 1969;Fountain et al, 1998;Klingler et al, 1991;Logothetis et al, 1986;Rodin, 1991;Ropakiotis et al, 2000;Roth et al, 1986;Scollo Lavizzari et al, 1977;Tartura et al, 1980;Thomaides et al, 1992;Veldhuizen et al, 1983). …”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 98%
“…Several studies have suggested that TSD can be useful in activating IEDs in wakefulness, especially in patients with IGE (Degen et al, 1980;Degen et al, 1981;Degen et al, 1983;Degen et al, 1987;El-Ad et al, 1994;Fountain et al, 1998;Geller et al, 1969;Klinger et al, 1991;Pratt et al, 1968;Ropakiotis et al, 2000;Roth et al, 1986;Scollo Lavizzari et al, 1977;Tartura et al, 1980;Veldhuizen et al, 1983). Fountain et al (1998) found that 7% of subjects had IEDs during wakefulness only after TSD.…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 99%